Connecting MASTERS Project: Mathematics and Science Teaching Excellence in Rural Schools - Karla M Childs (The Advocate, 2019)
This study examined the effects of a focused professional development program for teachers in rural schools on math content knowledge and persistence measured by outcomes on the Math Assessment. Scores for all participants were analyzed (n = 37). A marked improvement was seen in the math content knowledge of teachers from the pre-assessment to the post assessment. Teachers increased their scores by 17% on the Math Assessment. The most salient result of the present study pertained to the number of answers that were scored a zero meaning they were left blank with no attempt to answer. Noteworthy is the fact that there was a total of 23 scores of zero in the pre-assessments and only 5 scores of zero in the post assessments.
Keywords: STEM; Mathematics Education; Professional Development